Bibliometric Analysis of Hydrogels from Graphene Oxide Nanoparticles Using the VOSviewer Application - Diah Indriati; Asep Bayu Dani Nandiyanto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
This study aims to examine the development of research on hydrogels from graphene oxide nanoparticles published in Google Scholar from 2013 to 2022 (September) through a bibliometric computational analysis approach using the Publish or Perish and VOSviewer applications. The title, publication type, abstract, keywords, and range of years are the parameters used to select the data taken in the Publish or Perish application. Two hundred twenty-seven articles that are relevant to the desired theme. From year to year, there is an increase in the number of scientific publications related to hydrogels from graphene oxide nanoparticles to a peak in 2021, with as many as 46 articles; the following year, it decreased slightly to 31 articles. Topics of discussion widely raised in nanoparticle hydrogel research include synthesis, characterization, doping, application, and industrial-scale production. From this data, it appears that there is still an opportunity to continue to do more research related to hydrogels from graphene oxide nanoparticles, assisted by the VOSviewer application, which can also help to find problem topics that can be used as research innovation materials on hydrogels from graph oxide nanoparticles in the future.